The Adipokinetic Peptides of Hemiptera: Structure, Function, and Evolutionary Trends - Gäde, Gerd; Marco, Heather G. (Frontiers in Insect Science, 2022)
The Hemiptera comprise the most species-rich order of the hemimetabolous insects. Members of a number of superfamilies, most notably especially the more basal ones such as white flies, psyllids and aphids, belong to the most destructive agricultural insects known worldwide. At the other end of the phylogenetic tree are hemipterans that are notorious medical pests (e.g. kissing bugs). Most of the hemipteran species are good flyers, and lipid oxidation plays a pivotal role to power the contraction of flight muscles and, in aquatic water bugs, also deliver the ATP for the extensive swimming action of the leg muscles. Mobilization of stored lipids (mostly triacylglycerols in the fat body) to circulating diacylglycerols in the hemolymph is regulated by a set of small neuropeptides, the adipokinetic hormones (AKHs). We searched the literature and publicly available databases of transcriptomes and genomes to present here AKH sequences from 191 hemipteran species. Only few of these peptides were sequenced via Edman degradation or mass spectrometry, and even fewer were characterized with molecular biology methods; thus, the majority of the AKHs we have identified by bioinformatics are merely predicted sequences at this stage. Nonetheless, a total of 42 AKH primary sequences are assigned to Hemiptera. About 50% of these structures occur also in other insect orders, while the remaining 50% are currently unique for Hemiptera. We find 9 novel AKHs not shown to be synthesized before in any insect. Most of the hemipteran AKHs are octapeptides (28) but there is an impressive number of decapeptides (12) compared to other speciose orders such as Diptera and Lepidoptera. We attempt to construct a hypothetical molecular peptide evolution of hemipteran AKHs and find quite a bit of overlapping with current phylogenetic ideas of the Hemiptera. Lastly, we discuss the possibility to use the sequence of the aphid AKH as lead peptide for the research into a peptide mimetic fulfilling criteria of a green insecticide.